Dicentric chromosome in the bone marrow of a child with megakaryoblastic leukaemia and Down's syndrome. Issue 4 (April 1988) - Wilkie, A O; Kitchen, C; Oakhill, A; Howell, R T; Berry, P J
Abstract : A two year old girl with Down's syndrome (constitutional karyotype: 47 + 21), presenting with pancytopenia, developed acute megakaryoblastic leukaemia (AMKL). Her bone marrow contained an abnormal clone with a novel dicentric chromosome derived from chromosomes 5 and 7 (karyotype 46, XX, -5, -7, +dic (5;7) (p 13; p 11.2), +21. This case provides further evidence for a connection between chromosome 21 and this unusual form of childhood leukaemia, and raises questions about the loss of short arm material from chromosomes 5 and 7 compared with the more usual monosomy or long arm loss.